Motivational interviewing in obesity reduction - Szczekala, Katarzyna M.; Ślusarska, Barbara J.; Goś, Anna B. (Medical Studies/Studia Medyczne, 2017)
Motivational interviewing (MI) is a clinical, person-centred way of talking about change based on cooperation and aimed at strengthening a person, enhancing their motivation, and commitment to change. The phenomenon of the type of communication lies in its interdisciplinary character and effective application in health promoting education. The purpose of the article is to present the method of MI and possibilities of using it in the practice of obesity reduction on the basis of literature review reports on MI in health promotion delivered in the databases of, among others, PubMed and Scholar Google. The numerous research findings prove that MI is an effective intervention, which activates and supports people in the process of change due to bolstering their self-awareness, self-efficacy, and motivation, which, consequently, favours the effort made to achieve or maintain health. The potential of the approach in health promotion relies on the vast array of its application.